Enhancing the learning and transfer of preprocedural communication skills during clerkship using audio-visual material: a prospective case-controlled study over 2 years. Issue 1 (5th January 2022) - Chiang, Dung-Hung; Chen, Chung-Ting; Wang, Tse-Yao; Yang, Ying-Ying; Huang, Chia-Chang; Li, Tzu-Hao; Huang, Shiau-Shian; Kao, Shou-Yen; Chen, Chen-Huan; Hou, Ming-Chih; Sheu, Wayne Huey-Herng
Abstract : Objective/design/setting: This study aims to develop preprocedural communication-specific framework that emphasises the use of audiovisual materials and compares its acceptability by trainees with a regular module. Trainees: Between October 2018 and July 2021, 96 medical clerks were enrolled and randomly divided into regular and intervention groups. Another 48 trainees whose did not join the framework-based training but complete self-assessments were enrolled as the control group. Interventions: In the intervention training module, the key steps of preprocedural communication-specific skills were structuralised into a framework using the acronym of OSCAR. Primary and secondary outcome measures: This study compared the acceptability of trainees for two modules by measuring the degree of increase in the end-of-rotation and follow up (4 weeks later) competency from baseline by trainees' self-assessments and physician assessments after serial trainings. Results: In comparison with regular group trainees, greater degree of improvements (framework-1 statement: 111%±13% vs 27%±5%, p<0.001; framework-2 statement: 77%±9% vs 48%±2%, p<0.05; skill-1 statement: 105%±9% vs 48%±3%, p<0.001); skill-2 statement: 71%±11% vs 50%±9%, p<0.05) were noted in the framework-related and skill-related statement 1–2 (the familiarity and confidence to use the framework and skills) than those of intervention group. At the end-of-rotation stage, the trainees ability to use the 'A -step: using audiovisual materials' of the OSCAR was significantly improved (229%±13%, p<0.001), compared with other steps. In the intervention group, the degree of improvement of the end-of-rotation data of trainees' self-assessment from baseline was significantly correlated with the degree of the improvement in physicians' assessment data in the aspects of skills, framework and steps in framework (R=0.872, p<0.01; R=0.813, p<0.001; R=0.914, p<0.001). Conclusions: The OSCAR framework-based intervention module is well accepted by medical clerks and motivates them to integrate the acquired skills in clinical practice, which leads to trainees' primary care patients being satisfied with their preprocedural communication.